Global Tourism Watch 2008 - Canadian Tourism Commission; Destination Canada (Borealis, 2008)
The Canadian Tourism Commission (CTC) began conducting the annual Global Tourism Watch (GTW) program in 2007 to expand consumer-based intelligence in its core markets. In 2008, the second year of the program, the GTW was implemented in nine global markets – the US, Mexico, the UK, France, Germany, Australia, Japan, China and South Korea. The Year 2 research was co-funded by a partner group including British Columbia, Alberta, Saskatchewan, Manitoba, Ontario, Québec and the North (Yukon and Northwest Territories). The GTW program was designed to monitor and report on key market indicators for Canada, track brand performance and examine Canada's market positioning over time, and across all core markets, in a consistent way. The overall objectives of the GTW study are to: monitor key performance indicators, track response to Brand Canada, identify and track product opportunities and provide input into strategic market plans.